Assessment of online interaction pattern using the Q-4R framework - Shriram , Raghunathan; Kaur, Abtar (2011)
Online learning has merged into mainstream education as it allows learners to work at their own pace, get personalized attention and interact in a structured manner. The role of interaction is crucial in this process andvarious methods have been proposed in literature (Marcelo and Perera, 2007) to analyze its role in online learning. The purpose of this paper is to present findings on analysis of the linkages between interaction patterns, task given and facilitation methods in an online learning environmentA model of interaction patterns called Q-4R framework is proposed and, the experiences of 16students of the Master of Instructional Design & Technology programme at the Open University Malaysia werestudied. The flow of interactions in two comparable courses was explored for a period of two months each and evaluated. The study has thrown significant conclusions that can help us further understand the progression in interaction patterns over a period of time inadvertently aiding lifelong learning. (Abstract by authors)